Three Meetings in One Even, March 31-April 6, 2012, New Delhi, India - Vesna Vučinić-Nešković (University of Belgrade, 2016)
Three Meetings in One Event: 2012 World Council of Anthropological Associations Bi-Annual Meeting, Anthropology of Global Issues International Symposium, and Association of Social Anthropologists of the UK and Commonwealth Annual Conference. March 31-April 6, 2012, New Delhi, India